Sejarah Islam Indonesia dalam Perspektif Hamka - Jacky Zakaria; Muhammad Irfan Wahid (Syams: Jurnal Kajian Keislaman, 2020)
This paper explores the history of Indonesian Islam from Hamka’s perspective, especially regarding the history of the entry of Islam in Indonesia in general and the history of the entry of Islam in West Sumatra in particular, as well as the contribution of Hamka’s thoughts to the historiography of Indonesian Islam. Hamka, who is more famous as a scholar and writer, is also a historian. Hamka produces historical works on the history of Indonesian Islam. Moreover, Hamka’s knowledge on history is self-taught by reading history books. The author uses data sources consisting of primary sources and secondary sources obtained through library research. The historical methods used are heuristics (data collection), verification (source criticism), interpretation (data interpretation), and historiography (history writing). The article concludes that Hamka’s thoughts on the history of Indonesian Islam are illustrated by his theory regarding the history of the entry of Islam in Indonesia which is called the Mecca theory. Islam that existed in the archipelago in the 7th century spread to several areas in West Sumatra such as Ulakan, Pariaman, Minangkabau, and so on. Islam easily adapts to local culture and even becomes part of existing customs.